How Gentle Must Violence Against Women Be in Order to Not Be Violent? Rethinking the Word "Violence" in Obstetric Settings. (June 2021) - Lappeman, Maura; Swartz, Leslie
With the growing concern of human rights in health, the word "violence" is being used to describe apparent disrespectful treatment received by women by either health care practitioners or health care systems. As the definition of violence in health care settings broadens, questions arise over the impact of the term in describing objective reality. Specifically, does use of the term "violence" inadvertently disempower the women that it is meant to empower? This article explores the changing use of the term "violence" and specifically draws on evidence in a South African labor ward, where phenomena such as silence and limited social support have cultural underpinnings that contradict labels of structural or obstetric violence. As global research on obstetric violence in disadvantaged communities grows, choice of terminology will become more important in filtering results into medical policy and practice.